Radicular Cyst Associated with a Maxillary Deciduous First Molar: A Therapeutic Case Report - M Asadi; S Farhadi; K Gharanizadeh; S Tavasoli-Hojjati; S Ghadimi (Islamic Azad University, 2020)
Background: Radicular cysts are the most frequent odontogenic cysts of the jaws. Radicular cysts arising from the primary teeth are very rare and comprise 0.5% to 3.3% of radicular cysts in both primary and permanent dentitions. Case Presentation: In this paper, we report the clinical, radiographical, and histological characteristics of a radicular cyst associated with a maxillary deciduous first molar. The treatment plan included extraction and enucleation of the cyst under local anesthesia after the elevation of a mucoperiosteal flap, which led to satisfactory and uneventful healing. Conclusion: Early diagnosis of radicular cysts associated with the primary dentition allows for a less aggressive treatment plan and prevents adverse effects on the permanent successor.